E-LABS – ADVANCED E-LEARNING - Nowak, Jarosław; Pcian, Mieczysław (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2017)
The aim of this article is to describe the development of distance learning techniques which opened the possibilities of conducting laboratory activities. In effect there emerged e-labs used for practical activities in the form of e-learning. Laboratory devices are remotely controlled, their management is accomplished via the Internet. This article presents exemplary e-labs, where students participate in didactic activities, allowing university teachers to do research and perform experiments. Some of the presented e-labs can be used to conduct experiments for persons who are logged in as “visitor”.